2009
DOI: 10.1371/annotation/e82f810e-738a-47e5-9295-5a0cc9a0dc6c
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Interpain A, a Cysteine Proteinase from Prevotella intermedia, Inhibits Complement by Degrading Complement Factor C3

Abstract: Periodontitis is an inflammatory disease of the supporting structures of the teeth caused by, among other pathogens, Prevotella intermedia. Many strains of P. intermedia are resistant to killing by the human complement system, which is present at up to 70% of serum concentration in gingival crevicular fluid. Incubation of human serum with recombinant cysteine protease of P. intermedia (interpain A) resulted in a drastic decrease in bactericidal activity of the serum. Furthermore, a clinical strain 59 expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Several other bacterial proteases have been shown to cleave C3. Potempa and coworkers reported that interpain A, a cysteine protease of Prevotella intermedia, degrades the ␣-chain of C3 (22). Kuo and coworkers (15) have shown streptococcal pyrogenic exotoxin B to degrade ␣, ␣Ј (a 41-kDa fragment of the ␣-chain), and the ␤-chain of C3 effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several other bacterial proteases have been shown to cleave C3. Potempa and coworkers reported that interpain A, a cysteine protease of Prevotella intermedia, degrades the ␣-chain of C3 (22). Kuo and coworkers (15) have shown streptococcal pyrogenic exotoxin B to degrade ␣, ␣Ј (a 41-kDa fragment of the ␣-chain), and the ␤-chain of C3 effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Aquemethaemoglobin is further completely broken down and hame is released to generate black-colored Fe(III) protoporphyrin IX pigment [ 40 , 41 ]. Interpain A also disturbs immune reaction of the host by degrading complement factor C3 [ 42 ]. The counterpart gene is identified in other Prevotella intermedia strains and its homologous proteins are found in Prevotella nigrescens and Prevotella pallens .…”
Section: Resultsmentioning
confidence: 99%
“…Many bacteria of the Bacteroidales order [142] have a SpeB homolog, a peptidase capable of cleaving many immunologically relevant proteins. In particular, the periodontal pathogen Prevotella intermedia has a homolog interpain A that takes part in the inhibition of the immune response through complement degradation [144].…”
Section: Effects Of Se and Intebio ® On Cecal Microbiome Profilesmentioning
confidence: 99%